2021
DOI: 10.1186/s12876-021-01832-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of thromboelastography profile with severity of liver cirrhosis and portal venous system thrombosis

Abstract: Background and aim Hemostasis profile is often complicated in liver cirrhosis. Thromboelastography is a global viscoelastic test recommended by the current practice guideline and consensus. This cross-sectional study aimed to evaluate the association of thromboelastography profile with severity of liver cirrhosis and presence of portal venous system thrombosis (PVST). Methods Overall, 116 and 50 cirrhotic patients were included in the Shenyang and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
(49 reference statements)
0
9
0
Order By: Relevance
“…Evidence suggests that an imbalance of pro‐ and anti‐coagulants, such as an increased ratio of factor VIII and protein C, causes a hypercoagulable state, 43 but may not be associated with the presence of PVST in cirrhosis 44,45 . Similarly, most published studies, 14,46,47 except the one by Huang et al, 48 did not find any hypercoagulable state indicated by R alone in cirrhosis with PVST. In addition, nearly all published studies did not show any hypercoagulable state indicated by MA alone in cirrhosis with PVST, 14,46–48 although clot strength could discriminate non‐cirrhotic PVST (AUROC = 0.824 ± 0.112, p = 0.006) 47 and was sensitive for predicting venous thromboembolism in patients with critically ill coagulopathy, defined as thrombocytopenia and/or elevated INR or prolonged activated partial thromboplastin time 49 .…”
Section: Teg Profile and Portal Venous System Thrombosis In Liver Dis...mentioning
confidence: 89%
See 4 more Smart Citations
“…Evidence suggests that an imbalance of pro‐ and anti‐coagulants, such as an increased ratio of factor VIII and protein C, causes a hypercoagulable state, 43 but may not be associated with the presence of PVST in cirrhosis 44,45 . Similarly, most published studies, 14,46,47 except the one by Huang et al, 48 did not find any hypercoagulable state indicated by R alone in cirrhosis with PVST. In addition, nearly all published studies did not show any hypercoagulable state indicated by MA alone in cirrhosis with PVST, 14,46–48 although clot strength could discriminate non‐cirrhotic PVST (AUROC = 0.824 ± 0.112, p = 0.006) 47 and was sensitive for predicting venous thromboembolism in patients with critically ill coagulopathy, defined as thrombocytopenia and/or elevated INR or prolonged activated partial thromboplastin time 49 .…”
Section: Teg Profile and Portal Venous System Thrombosis In Liver Dis...mentioning
confidence: 89%
“…There is a correlation between TEG parameters and CCTs, 12,13 but haemostatic status indicated by CCTs and TEG is often inconsistent in patients with liver disease. Normal haemostatic status indicated by R and MA in cirrhotic patients is more common than that indicated by PT and PLT 12,14 . In a proportion of cirrhotic patients with increased INR, TEG profile is within the normal range 15 .…”
Section: Teg Versus Cctsmentioning
confidence: 98%
See 3 more Smart Citations